ASPEK HUKUM PERDATA DALAM PENYIARAN DAN PENAYANGAN IKLAN DI TELEVISI DI TVRI SUMUT - Hidayani, Sri (Universitas Medan Area, 2016)
Television is one of the broadcasters in the form of broadcasts as set out in Article 1 paragraph 1 of Law 32 of 2002 on Broadcasting which reads